2019
DOI: 10.1002/bdr2.1594
|View full text |Cite
|
Sign up to set email alerts
|

Fetal sex discordance between noninvasive prenatal screening results and sonography: A single institution's experience and review of the literature

Abstract: Background With the increasing availability of noninvasive prenatal screening (NIPS) and high‐resolution ultrasound, more cases of sex discordance are being identified in routine clinical practice. This can be a source of much concern for families and clinicians. Knowledge about the limitations of NIPS and reasons for discordant results are critical for counseling parents. Aims Here, we present three cases from a single tertiary care referral center. We also review the literature to address potential limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Another study 30 also reported 3 cases of sex inconsistency between NIPT and ultrasound results, and they suggested further examination and invasive prenatal diagnostic tests in cases with inconsistent results in sex assessment between NIPT and ultrasound. However, in China, sex is not allowed to be determined by NIPT, and therefore, it is impossible to obtain information about sex inconsistency between NIPT and ultrasound examination before birth.…”
Section: Discussionmentioning
confidence: 96%
“…Another study 30 also reported 3 cases of sex inconsistency between NIPT and ultrasound results, and they suggested further examination and invasive prenatal diagnostic tests in cases with inconsistent results in sex assessment between NIPT and ultrasound. However, in China, sex is not allowed to be determined by NIPT, and therefore, it is impossible to obtain information about sex inconsistency between NIPT and ultrasound examination before birth.…”
Section: Discussionmentioning
confidence: 96%
“…After excluding the common explanations for discordance, invasive testing should be offered to confirm the genetic sex and evaluate for the presence of the SRY gene and pathogenic copy number variants on a microarray. A gene panel can look for common pathogenic mutations when a DSD is suspected [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al [40] demonstrated for the first time that maternal genomic materials could affect NIPT accuracy. Afterward, many studies demonstrated that maternal factors could significantly affect the accuracy of NIPT for fetal SCAs [8, [16][17][18][19][20][21][22][23][24]41]. Wang et al [8] reported that maternal X chromosome aneuploidy and mosaicism were responsible for approximately 8.6% of discordant NIPT results for SCAs.…”
Section: Discussionmentioning
confidence: 99%
“…The positive predictive value (PPV) of SCAs screening was consistently lower in respect of autosomal trisomies. This could be related to confined placental mosaicism (CPM), abnormal maternal SCAs, including full maternal SCA, mosaic maternal SCA, and maternal copy number variants, as well as loss of an X chromosome from maternal cells as a natural part of aging [16][17][18][19][20][21][22]. Therefore, there is a lack of reliable data on SCA rates.…”
Section: Introductionmentioning
confidence: 99%